Students' perceptions of the nurse's work in the family health strategy - Pablo Ramon Carloni; Flávio Adriano Borges; Natália Sevilha Stofel; Márcia Niituma Ogata; Larissa de Almeida Rézio; Ariane Tufaile de Paiva (Universidade Federal do Ceará, 2021)
Objective: to understand the perceptions of nursing students about the work of nurses in the Family Health Strategy. Methods: qualitative research developed with 19 students from different periods of the undergraduate nursing course. Semi-structured interviews were carried out, proceeding, after being organized, to thematic analysis and confrontation with some concepts of Institutional Analysis. Results: the data analysis gave rise to three themes: 1) Students' perceptions of the nurse's work process, 2) The bond in the nurse's work and 3) Structural and relational limits of the nurse's work. Conclusion: the nurse's work in the Family Health Strategy is something in constant institutionalization process, requiring a range of theoretical and scientific knowledge and skills that are expressed through autonomy and bond with users. However, it faces some crossings such as the scarcity of infrastructure, human and material resources and the difficulty in teamwork.